Stop Blaming Milton Friedman! - Brian R. Cheffins (Washington University Law Review, 2021)
A 1970 New York Times essay on corporate social responsibility by Milton Friedman is often said to have launched a shareholder-focused reorientation of managerial priorities in corporate America. The essay correspondingly is a primary target of a rapidly growing group of critics of the present shareholder-centric approach to corporate governance. This article argues that it is erroneous to blame (or credit) Milton Friedman for the rise of shareholder primacy in American corporations. In order for Friedman’s views to be as influential as has been assumed, his essay should have constituted a fundamental break from prevailing thinking that changed minds with some alacrity. In fact, what Friedman said on corporate purpose was largely familiar to readers in 1970 and his essay did little to change managerial priorities at that point in time. The shareholder-first mentality that would come to dominate in corporate America would only take hold in the mid-1980s. This occurred due to an unprecedented wave of hostile takeovers rather than anything Friedman said and was sustained by a dramatic shift in favor of incentive-laden executive pay. Correspondingly, the time has come to stop blaming him for America’s shareholder-oriented capitalism.
Keywords: Milton Friedman; Corporate law; Shareholder primacy; Corporate governance; Corporate purpose; Shareholder value